1980
DOI: 10.1111/j.1600-0773.1980.tb01572.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Fluoride Sensitivity of Liver Cells from Rats Chronically Exposed to Fluoride

Abstract: Absrruct:The fluoride sensitivity, determined as effect on protein synthesis (incorporation of "C-leucine), of liver and kidney cells in suspension culture was explored. The cells were freshly prepared by collagenase perfusion from rats given drinking water with or without addition of 100 p.p.m. (5.26 mM) fluoride for 9-28 weeks. The fluoride sensitivity of the liver cells from rats given fluoridated water for more than 9 weeks was decreased compared to cells from control rats, whereas the fluoride sensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1983
1983
1985
1985

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…We have previously reported that longer-term exposure of rats to NaF resulted in decreased fluoride sensitivity (inhibition of the rate of protein synthesis) of the liver cells from such animals (Hongslo et al 1980), probably developed as an adaptive response to the fluoride exposure. In the present study, the plasma GOT of the NaF exposed rats ( 6 7 f 2 0 UI/l, n=10) was not significant different from that of the control rats ( 5 8 f 1 8 Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously reported that longer-term exposure of rats to NaF resulted in decreased fluoride sensitivity (inhibition of the rate of protein synthesis) of the liver cells from such animals (Hongslo et al 1980), probably developed as an adaptive response to the fluoride exposure. In the present study, the plasma GOT of the NaF exposed rats ( 6 7 f 2 0 UI/l, n=10) was not significant different from that of the control rats ( 5 8 f 1 8 Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…It is unlikely that fluoride itself is a genotoxic carcinogen (IARC 1982), but it cannot be excluded that it may modulate the effect of complete carcinogenic substances. It has been reported that low levels of NaF can accelerate tumour growth (Taylor & Taylor 1965), and exposing rats to fluoride may evoke several biochemical changes in the liver (Shearer 1974;Hongslo et al 1980).…”
mentioning
confidence: 99%
See 1 more Smart Citation